Analisis Fiqh Siyasah Terhadap Peran Hakim Pengawasan dan Pengamatan Berdasarkan Pasal 277 j.o Pasal 280 KUHAP - Putra, Farandi Wiryanata; Frenki, Frenki; Vinanda, Olivia Rizka (Syekh Ali Hasan Ahmad Addary State Islamic University, 2025)
This research discusses the Fiqh Siyasah Analysis of the Role of Supervision and Observation Judges based on Pasal 277 jo Pasal 280 of UU Number 8 of 1981 concerning Criminal Procedure Law (KUHAP) at the Menggala Class IIB District Court of Tulang Bawang Regency. The focus of this study is to evaluate the implementation of the judge's function in supervising the implementation of court decisions and reviewing its suitability with the principles of fiqh siyasah. The research used descriptive qualitative methods with data collection techniques through interviews and documentation. The results showed that the implementation of the duties of supervisory judges and observations in the field still faced obstacles such as limited human resources, lack of technical understanding, and the absence of standardized operational guidelines. In the perspective of fiqh siyasah, this role is a shar'i mandate that aims to maintain substantive justice and protect the rights of prisoners. Optimizing this role is important to ensure the implementation of the law in accordance with sharia and universal values of justice. This research is expected to enrich the study of Islamic law, become an academic reference, and provide practical recommendations to improve the effectiveness of the implementation of Kimwasmat in court.